Autonomy in Abuse: Glimpses of Freedom in New Orleans. - Holcomb, Lisa (University of Wisconsin Oshkosh, 2006)
This paper examines unusual opportunities for autonomy found by women of African descent in New Orleans, from the time the city was acquired by the United States until the Civil War. This city's unique history partially explains the availability of such options. The rest is revealed through an examination of individual women who actively claimed personal freedoms. The independence they grasped is illustrated in a variety of contexts: from slave women suing for manumission to prostitutes seeking monetary self-sufficiency. Every woman who sought independence also exposed herself to inherent risks. The hazards and benefits found within white society were greater than those found in the African American community. Whatever avenue the women chose to pursue, they tested and explored the limits of the society they inhabited in a search for forms of independence.
Keywords: African American women -- New Orleans (La.); Women, Black -- United States -- Social conditions -- 19th century